Histomorphometric assessment of implant coated with mixture of nano-alumina and fluorapatite in rabbits - Sabreen Waleed Ibrahim; Aula Kamal Rafeeq; Mustafa Sabah Ahmedhamdi (Saudi Dental Journal, 2021)
Background: The application of nanoscale surface modification was found to be useful in the improvement of osseointegration of endosseous dental implants. The fluorapatite (FA)/alumina (Al2O3) mixture is recognized for its outstanding bioinertia and can significantly increase the biocompatibility and bioactivity of biomaterials. Objective: The aim of the present work was to evaluate the bone response to nano-alumina- and fluorapatite-coated dental implants using rabbit tibiae. Material and Methods: The coating was performed using the dip-coating method. Commercially pure titanium screw-type implants were used as a control group. The coated implants were the experimental group. Each group consisted of 12 screws that were surgically implanted in 6 healthy New Zealand rabbits. Histological and histomorphometric evaluations were performed at the bone to implant contact (BIC) interface, bone fraction area occupancy (BAFO) and fibrous tissue at 2 and 6 weeks of healing. Results: This analysis showed that the coated implants had more rapid osseointegration than the control group, with a significant difference after 2 and 6 weeks of healing for both groups. The histomorphometric evaluation demonstrated higher values for BIC% and BAFO% and lower values of fibrous tissue in the mixture-coated Ti implants than in the control group. Conclusion: The current study suggested that the nano-alumina and fluorapatite mixture coating is a favourable candidate for rapid osseointegration over uncoated implants.